2018
DOI: 10.1080/08820139.2018.1552360
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells at the Intersection of Inflammaging and Bone Fragility

Abstract: Age-related alteration of the immune system with aging, or immunosenescence, plays a major role in several age-associated conditions, including loss of bone integrity. Studies over the past several years have clearly established the immune system is chronically activated with advanced aging, termed inflammaging, and is characterized by elevated levels of proinflammatory cytokines in response to physiological or environmental cues that essentially result in an arrested immune system that maintains a low-level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…We provide the first evidence suggesting that when myeloid‐derived suppressor cell populations are expanded with simultaneous suppression of T‐cell and B‐cell populations, there is spontaneous alveolar bone loss 60 . In addition, we have shown that monocytic myeloid‐derived suppressor cells (CD11b + Ly6C hi Ly6G) possess cellular plasticity by virtue of their ability to form mature osteoclasts 62 . In this conceptual perspective, we offer a novel “two‐hit” model to explain obesity‐exacerbated alveolar bone destruction.…”
Section: Current Perspectivementioning
confidence: 81%
“…We provide the first evidence suggesting that when myeloid‐derived suppressor cell populations are expanded with simultaneous suppression of T‐cell and B‐cell populations, there is spontaneous alveolar bone loss 60 . In addition, we have shown that monocytic myeloid‐derived suppressor cells (CD11b + Ly6C hi Ly6G) possess cellular plasticity by virtue of their ability to form mature osteoclasts 62 . In this conceptual perspective, we offer a novel “two‐hit” model to explain obesity‐exacerbated alveolar bone destruction.…”
Section: Current Perspectivementioning
confidence: 81%
“…MDSCs are expanded and activated by a number of pro-inflammatory and infectious stimuli and inhibit T cells and innate immune functions of other myeloid cells via release of ROS, NO, and enzymes such as arginase-1 [ 71 ]. Several groups have shown that MDSCs can also differentiate into OCs and contribute to bone erosion in various noninfectious models [ 72 , 73 , 74 , 75 ], so they likely have the potential to cause tissue damage in iOM ( Figure 2 ). In mouse models of prosthetic-associated S. aureus biofilms, MDSCs have been shown to accumulate at higher rates than neutrophils and macrophages, but their role in disease progression is likely complex.…”
Section: Immune Modulation By Ocs and Their Conventional And Unconmentioning
confidence: 99%
“…And the prolonged and marked expansion of the IMCs lead to the expansion of MDSC population (Gabrilovich and Nagaraj, 2009). Several reports support MDSC plasticity as osteoclast progenitors under various pathological conditions associated with bone destruction (Sawant et al, 2013;Zhang et al, 2015;Kirkwood et al, 2018). Therefore, to study whether the specificity of mandibular bone is due to the heterogeneity of bone marrow cells, it is necessary to explore not only the populations of lineage committed bone marrow cells but also their progenitors.…”
Section: Introductionmentioning
confidence: 99%